R. Bohlin, De Osynliga. Det Europas fattiga arbetarklass; M. Linton, De hatade. Om radikalhögerns måltavlor; B. Elmbrant, Europas stålbad. Krisen som slukar välfärden och skakar euron (All titles by Atlas, Stockholm, 2012) - Monica Quirico (Nordicum-Mediterraneum, 2014)
A review of the following volumes: Bohlin, Rebecka (2012), De Osynliga. Det Europas fattiga arbetarklass (The invisibles. Europe’s poor working class), Stockholm: Atlas; Linton, Magnus (2012), De hatade. Om radikalhögerns måltavlor (The hated. About the targets of the radical right), Stockholm: Atlas; Elmbrant, Björn (2012), Europas stålbad. Krisen som slukar välfärden och skakar euron (Europe’s baptism of fire. The crisis swallowing Welfare State and shaking euro), Stockholm: Atlas.